PENGARUH SUPERVISI AKADEMIK, BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KOMPETENSI PROFESIONAL GURU SMP NEGERI NEGERI DI KECAMATAN JEPARA KABUPATEN JEPARA - Fatkhur Sugiatmoko; Ngasbun Egar; Ghufron Abdullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to test and analyze: (1) the influence of the principal's academic supervision on teacher professional competence; (2) the influence of work culture on teacher professional competence; (3) the influence of teacher work motivation on teacher professional competence; (4) the influence of the principal's academic supervision, work culture, and teacher work motivation on teacher professional competence. Population 251 people, sample 154 people. The instrument test used is validity and reliability test. The classical assumption test uses normality test, linearity test, multicollinearity test, and heteroscedasticity test. Data analysis uses multiple linear regression test, F test (ANOVA) and t test. Based on the results of the study, it can be concluded as follows: (1) Academic Supervision has a positive and significant effect on Teacher Professional Competence. This is based on the results of the t test, proven by the results of t count ≥ t table, namely 11.388> t table 1.65, and the Sig value (2-tailed) 0.000 <0.05; (2) Work Culture has a positive and significant effect on Teacher Professional Competence. This is based on the results of the t-test, proven by the calculated t of 8.796 > t table 1.65, and the Sig value (2-tailed) 0.000 < 0.05; (3) Work Motivation has a positive and significant effect on Teacher Professional Competence. This is based on the results of the t-test, proven by the calculated t ≥ t table 6.650 ≥ 1.6509, and the Sig value (2-tailed) 0.000 < 0.05; (4) Academic Supervision, Work Culture and Work Motivation simultaneously have an effect on the variable of Teacher Professional Competence, obtained by the calculated F of 80.582 with a significance level of 0.000. The calculation results obtained the calculated F value > F table (80.582 > l2.66) and the significance value is 0.000 < 0.005.